Esnaola contra Rosas. (Revista Argentina de Musicología, 2018)
Argentine pro-Rosas or revisionist historiography tends to consider Juan P. Esnaola as a party member of the Buenos Aires governor, Juan M. de Rosas. The composer’s biographers were more cautious, and for a good reason. A minute examination of his life on the basis of documents both well-known and newly-found does not yield any argument to support his sympathies for the ruler. On the contrary, a plethora of clues of a different nature suggests that Esnaola was an opponent of the regime. This idea stems out of the imprisonment that he suffered by Rosas’s order, documented here for the first time in detail; and out of gestures in his compositions, sometimes minimal in size but always remarkable in kind, which this article interprets as a projection of images critical to the governor, in terms of negative allegory (in the song La risa de la beldad), ironic representation (in three encomiastic anthems dedicated to Rosas), and moral condemnation (in the Lamentations for choir and orchestra, Heth. Cogitavit Dominus). In the final analysis, it becomes possible to understand Esnaola only as a subject fractured by the government’s brutality, which lead him to use masks, both personal and musical, to disguise dangerous convictions; he thus converted himself into one of the relatively numerous “crypto-unitarians” of Buenos Aires under the Rosas regime.
Keywords: Juan Pedro Esnaola; Juan Manuel de Rosas; crypto-unitarian; dictatorship; political expression